PEMETAAN PERSEPSI INVESTOR ATAS INVESTASI REKSA DANA PUBLIK DENGAN METODE MULTIDIMENSIONAL SCALING - Adhi, Nurseto; Sokawati, Dewi Bella; Sulistyorini, Utami Tri; Wijayanto, Edi (KEUNIS, 2022)
This study aims to map the position of public mutual fund products and investment managers based on the results of perceptual mapping. The samples used in this study were 5 public mutual funds and 9 investment managers in each type of public mutual fund based on the investment portfolio selected using the purposive sampling method. The method of analysis used descriptive statistical analysis and multidimensional scaling. The results of the data processing of the mutual fund product attributes are processed in Microsoft Excel which further passed through the statistical test stage of multidimensional scaling ALSCAL (Alternative Least Square Scaling) using the SPSS application. The result of the multidimensional scaling test show that the perceptual mapping is divided into 4 quadrants based on the determinant attributes of public mutual fund products. It found that 6 mutual fund products divided by Risk and Costs determinant attributes, then 6 other mutual fund products found divided by   NAB/UP and return, then 4 other mutual fund products found are not divided by determinant attributes and the rest 4 other mutual fund products divided by other determinant attribute in this research.